Impact of social determinants of health on obesity among American Indian and Alaska Native young adults - Kimberly R. Huyser; Angela G. Brega; Margaret Reid; Tassy Parker; John F. Steiner; Jenny Chang; Luohua Jiang; Amber L. Fyfe-Johnson; Michelle Johnson-Jennings; Vanessa Y. Hiratsuka; Nathania Tsosie; Spero M. Manson; et al. (PLoS ONE, 2025)
We examined the prevalence of obesity among American Indian and Alaska Native (AIAN) young adults and to investigate the association between key social determinants of health (SDOH) and higher body mass index (BMI). We used the Indian Health Service Improving Delivery Data Project from fiscal year 2013. It includes data for 20,698 AIAN young adults aged 18–24 years. We added county-level measures of SDOH from the USDA Food Environment Atlas and the Census as contextual variables. We conducted stratified logistic regressions to understand the relationship between these SDOH indicators and odds of obesity. Thirty-seven percent of our sample was identified as obese (i.e., BMI ≥30). Individuals who lived in counties with lower levels of educational attainment and higher levels of poverty had higher odds of obesity than those who lived in counties with higher education and lower poverty (p < 0.0001). Counties with higher poverty rates had less access to social and environmental resources than the lower poverty rate counties (p < 0.0001). Federal and state governments should increase access to education and economic development opportunities to positively impact health outcomes.